Acceptance of COVID-19 Vaccine Among Unvaccinated Filipinos - Pamela Pagador; Adrienne Pacleb; Mikaela J. Ormita; Frances E. Valencia; Danz H. Velasco; Rosemarie Josue-Dominguez (University Library System, University of Pittsburgh, 2022)
Background: Access to COVID-19 vaccines was one of the global measures for containing the COVID-19 pandemic. However, it is still not known whether Filipinos accept it.  Methods: Cross-sectional study based on a modified version of the community COVID-19 vaccine acceptance survey, disseminated and collected through Google Forms to Filipinos within the Philippines aged 18-65 years old. Multinomial logistic regression analysis was performed to determine the association between the willingness to be vaccinated and sociodemographic characteristics using odds ratios (OR) with 95% confidence intervals (95%CI).  Results: Among the 1,011 participants, 79.5% were willing to accept the COVID-19 vaccine. Significant determinants (p<0.05) were age, region of residence, sex, profession, income, religion, practice of alternative medicine, and previous contact with COVID-19 positive individuals. Essential healthcare workers (OR=11.0, 95%CI=1.3-93.5), practiced alternative medicine (OR=2.4, 95%CI=1.3-4.4), with previous contact with a COVID-19 positive person (OR=2.9, 95%CI=1.4-6.0), and females>males (OR=0.6, 95%CI=.3-1.0) were also more likely to accept COVID-19 vaccination. 63.7% preferred Pfizer the most, and 54.4% preferred Sinovac the least. In contrast, married individuals, essential non-healthcare workers and private/self-employed sectors were less likely to accept COVID-19 vaccines. Many individuals who refused to be vaccinated were unsure of its safety (59.70%) and had no trust in vaccines (56.50%). Conclusion: Despite a high prevalence of acceptance of the COVID-19 vaccine in our study, there were significant sociodemographic disproportions in vaccine acceptance. Better policies urging Filipinos to get vaccinated and more effective dissemination of unified information regarding vaccines from verified sources are recommended to boost vaccine confidence in the Philippines.